Mario Vargas Llosa’s the Time of the Hero: paradox of military man - Mohammad Safaei (Penerbit Universiti Kebangsaan Malaysia, 2020)
Mario Vargas Llosa’s The Time of the Hero, originally published in Spanish in 1963, depicts military life and its paradoxes in Leoncio Prado, a military high school that the Peruvian author attended in early 1950s. In this essay, I investigate the paradox of military man in regard to two systems of thought as well as two diverse ontologies. Drawing upon Gilles Deleuze’s metaphysics and his collaborative work with Félix Guattari, I explain, in specific, the properties of mass multiplicities versus pack multiplicities and their corresponding relation to the difference between a State army and its inherent war machine. I analyse the paradox of perceptions and praxis that each of these multiplicities is disposed to generate. Despite the military administration’s insistence on the development of organized behaviour and authentic identities, Leoncio Prado provokes the formation of packs with their inconceivable practices and modes of becoming that undermine the academy’s fundamental tenets. Vargas Llosa demonstrates that the event of becoming which, in this novel, exemplifies resistance against oppressive military norms proceeds along an unpredictable trajectory and culminates in the formation of cells with microfascist sentiments and economy. The emergence of a microfascist cell is a fundamental paradox and ironically the consequence of the military insistence on discipline and submission to authority. In some respects, the radicalization of packs results from initiation rites and other abusive practices that have historically been woven into the fabric of military training.